A comprehensive study to explore differences in mycotoxin patterns from agroecological regions through maize, peanut, and cassava products: a case study, Cameroon - Ediage, E.N.; Hell, K.; Saeger, S. (American Chemical Society, 2014)
A total of 420 samples were collected from agrarian households. Whereas 51% (215/420) of the samples were contaminated with one or more toxins, the contamination rates for maize, peanut, and cassava products were 74, 62, and 24%, respectively. The fumonisins (20?5412 ?g/kg), aflatoxin B1 (6?645 ?g/kg), roquefortine C (1?181 ?g/kg), and deoxynivalenol (27?3842 ?g/kg) were the most prevalent contaminants in maize. For peanut samples, aflatoxin B1 (6?125 ?g/kg) and ochratoxin A (0.3?12 ?g/kg) were the main contaminants, whereas aflatoxin B1 (6?194 ?g/kg) and penicillic acid (25?184 ?g/kg) were detected in the cassava products. Exposures calculated through maize intake for fumonisin B1 and aflatoxin B1 were several-fold higher (2?5 for fumonisin B1 and 104?105 for aflatoxin B1) than the health-based guidance values of 2 ?g/kg bw/day and 0.15 ng/kg bw/day, respectively. The study design constitutes a good model that can be implemented in other sub-Saharan African countries.